Konsep Murāqabah Dalam Al-Quran Sebagai Dasar Etika Pengawasan Cctv Di Era Society 5.0 - Gustina Fauzia; Yusuf Baihaqi; Siti Badiah; Andieni Putri Olivia Arifin (IAIN Padangsidimpuan, 2026)
The development of Closed-Circuit Television (CCTV)-based surveillance technology in the Society 5.0 era has created a dilemma between the need for public security and the protection of individual privacy. Smart surveillance systems integrated with big data and artificial intelligence are often implemented without an adequate ethical foundation. This article aims to analyze the concept of Murāqabah in the Qur'an as an ethical framework for CCTV surveillance in the digital era. This study employs a qualitative library research design using the Tafsīr Maudhū‘ī (thematic exegesis) approach. The primary data consist of Qur'anic verses related to Murāqabah Ilāhiyyah (Divine surveillance), the prohibition of tajassus (unlawful spying), and the principles of justice and trustworthiness. These data are analyzed thematically and conceptually with reference to both classical and contemporary Qur'anic exegeses. The findings reveal that Murāqabah in the Qur'an extends beyond the theological concept of Divine surveillance to cultivate moral consciousness that fosters self-control, responsibility, and integrity. The Qur'an establishes ethical boundaries for surveillance through the prohibition of tajassus and the principle of respecting individual privacy, emphasizing that public security must not be achieved at the expense of human dignity. In the context of CCTV surveillance, four core values emerge as the foundation of a digital ethics framework: murāqabah ilāhiyyah (Divine consciousness), amānah (trustworthiness), ʿadl (justice), and iḥsān (benevolence or moral excellence). This article contributes by formulating Murāqabah as an integrative paradigm of digital surveillance ethics, providing a relevant normative foundation for the development of more humane smart surveillance systems in the Society 5.0 era